EVENT STUDY: RESPOND OF RETURN STOCK ON INDONESIAN PRESIDENTIAL ELECTION IN 2024 STUDY CASE IN LQ-45 INDEX - Dita Dismalasari Dewi; Risqia Thufhil Laeli; Nurida Fitriani (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
Elections are a significant political occurrence that has a profound impact on a nation's economy. The capital market, as an economic instrument, is inherently influenced by both economic and non-economic environmental factors. The objective of this study was to examine the response of the Indonesian capital market to market anomaly events, specifically focusing on the 2024 Presidential Election. The stock market's reaction is assessed by the comparison of abnormal return and predicted return. The study focuses on the population of companies whose shares are listed in the LQ-45 index. This study employs the event study methodology. The data indicated that investors responded favorably over the four days preceding and following the Presidential Election on February 12, 2024. These characteristics suggest the presence of investor optimism over the scheduled date of the elections, which is February 12, 2024. There was a rise in the average amount of stock trading both before and after the presidential elections on February 12, 2024. Keywords: Reaction Capital Markets, Event Study, Abnormal Return, Expected Return, 2024 Presidential Election.